Effect of Step Aerobics Applied Early in Phase 2 Cabg Subjects on Functional Capacity and Exercise Tolerance (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: In recent years, cardiovascular accidents are rising due to improper diet, ill habits, uncontrolled cholesterol levels, stress, etc. Coronary artery diseases are in the leading cause of death. After a coronary artery disease like myocardial infarction the individual’s general health is week and the quality of life of these individuals is reduced and hence, morbidity starts building, causing reduced functioning and reduction in overall health and functional capacity. 30 individuals participated in this study who had undergone coronary artery bypass grafting and were under phase 2 of cardiac rehabilitation. The individuals had performed low intensity Step Aerobics for 12 weeks and were evaluated for the efficiency of step aerobics on functional capacity and exercise tolerance in such individuals. Objectives: To find the effect of step aerobics on the functional capacity and on exercise tolerance. Methodology: In this study, 30 subjects who had undergone CABG of age from 30-65 years. These individuals were selected on the basis of their inclusion criteria. They were treated with step aerobics as form of exercises for 12 weeks. After pre-post assessment, the data was analysed with help of proper statistical methods. Results: According to the result, there is extremely significant difference among the subjects six- minute walk test distance scores (p-value < 0.0001). Among the vitals assessed pre and post six-minute walk test, there was significant difference between the respiratory rate (p-value=0.0219), there was also very significant difference between the heart rate (p-value < 0.001). There was not quite significant change in the blood pressure levels i.e. systolic and diastolic p-value=0.0559 and 0.0862 respectively. Also, there was seen extremely significant difference in the peak O2 consumption levels according to DASI p-value < 0.0001) and also in the MET scores in DASI (p-value < 0.0001), making the difference to be extremely significant. Conclusion: The results obtained by studying the effects post treatment suggest that in rehabilitation of the CABG patients, implementation of step aerobics early has greater effects on functional capacity, exercise tolerance and general health including the quality of life.